Photovoice with the LGBTIQ community: a systematic review - Pinheiro, Daniela Sofia Ribeiro (2023)
Photovoice is a research method that uses photographs taken by participants to share, through narratives, their lives, and experiences. Over the years this method has been frequently used with marginalized populations. As is the case with the LGBTIQ community, a community made up of individuals of different sexual orientations and gender identities. In this review, articles reporting the use of photovoice with participants from the LGBTIQ community were analyzed, with the aim of understanding the potential of the methodology with this population, analyzing the advantages and disadvantages, and the topics that have been addressed. The results demonstrate that photovoice provides self-expression and gives voice and empowerment to people from sexual and gender minorities and has potential as an intervention strategy. However, using photovoice with this population can be a challenge both for ethical reasons and because some subjects are difficult to portray with photographs, or are not suitable for group discussion. Photovoice has been used to explore a wide range of topics in the LGBTIQ population, such as their experiences, identity, social relationships, resilience, social support, and health. It is therefore a method with the potential to work with vulnerable populations, being quite flexible and subject to adaptations.